Glassy carbon electrodes modified with multiwalled carbon nanotubes for the determination of ascorbic acid by square-wave voltammetry - Kumar, Sushil; Vicente-Beckett, Victoria (Beilstein Journal of Nanotechnology, 2012)
Multiwalled carbon nanotubes were used to modify the surface of a glassy carbon electrode to enhance its electroactivity. Nafion served to immobilise the carbon nanotubes on the electrode surface. The modified electrode was used to develop an analytical method for the analysis of ascorbic acid (AA) by square-wave voltammetry (SWV). The oxidation of ascorbic acid at the modified glassy carbon electrode showed a peak potential at 315 mV, about 80 mV lower than that observed at the bare (unmodified) electrode. The peak current was about threefold higher than the response at the bare electrode. Replicate measurements of peak currents showed good precision (3% rsd). Peak currents increased with increasing ascorbic acid concentration (dynamic range = 0.0047–5.0 mmol/L) and displayed good linearity (R2 = 0.994). The limit of detection was 1.4 μmol/L AA, while the limit of quantitation was 4.7 μmol/L AA. The modified electrode was applied to the determination of the amount of ascorbic acid in four brands of commercial orange-juice products. The measured content agreed well (96–104%) with the product label claim for all brands tested. Recovery tests on spiked samples of orange juice showed good recovery (99–104%). The reliability of the SWV method was validated by conducting parallel experiments based on high-performance liquid chromatography (HPLC) with absorbance detection. The observed mean AA contents of the commercial orange juice samples obtained by the two methods were compared statistically and were found to have no significant difference (P = 0.05).
Keywords: ascorbic acid; carbon nanotubes; glassy carbon electrode; square-wave voltammetry